Pengaruh pelatihan total quality management terhadap kinerja manajemen = The influence of total quality management training on management performance - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Background: TQM is a management approach that focuses on quality based on the participation of all members in order to satisfy customers. Bapelkes (Health Training Center) Gombong conducted TQM training for its members. The influence of the training on Bapelkes Gombong performance needs to be examined. Method: The research method was exploratory descriptive that used the EFQM (The European Foundation for Quality Management) approach. The research was carried out in Bapelkes Gombong and Bapelkes Salaman. The analysis units were Bapelkes Gombong that has done TQM training and Bapelkes Salaman, as control. The research subjects were the managers of both institutions. Predictor variable was TQM training. Criterion variables were Leadesrship, Policy and Strategy, People Management, People Satisfaction, Partnerships and Resources, Processes, Customer satisfaction, People satisfaction, Impact on society, Key performance results and the moderator variables were Middle management, Funding, Facilitator and Training method. Results: The research result showed that the management performance profile in Bapelkes Gombong increased significantly with regard to all performance management criteria. It was concluded that TQM training influenced management performance. However, the impact on society was higher at Bapelkes Salaman. The moderator variables decreased the relationships management performance.